IMPLEMENTATION OF THE SMART CLINIC PROGRAM IN DEVELOPING ACADEMIC SKILLS OF SLOW LEARNERS - Rahmah, Azizatur; Farisia, Hernik; Rizki Amaliyah, Nadia; Amaliatus Sholikha, Risma; Engrasia Febryantika, Arlynda; Husnah, Barizatul; Maulandini, Tristi (JPI (Jurnal Pendidikan Inklusi), 2024)
Children with slow learner characterized by a slow response in learning, completing assisgnment lately, short-term memory, lower learning achievement, and low motivation. In academic competencies, children with slow learner category faced special needs in reading, writing, and other academic compulsory, etc. Therefore, a program as Klinik Pintar “Smart Program” was implemented at Badrussalam Islamic Primary School in Surabaya. This study aims to reveal the implementation of klinik pintar in developing students’ academic capability with slow learner. This research used qualitative design with Miles and Huberman as the analyses technique. The results revealed that 2 children at Badrussalam Islamic primary school have been identified as children with special needs as slow learners. To accommodate their needs, the school implemented smart clinic program that focused on developing students’ ability in reading and writing. The activity conducted in this program implemented by considering students academic differentiation started from learning alphabet, words, and sentences. In improving writing competencies, students also learned how to use pencils, sitting position in learning, and doing exercise in writing to optimize students’ motoric skill. Keyword: Smart Clinic, Slow Learner, Academic Ability